Human haptoglobin phenotypes and concentration determination by nanogold-enhanced electrochemical impedance spectroscopy - Cheng, Tsai-Mu; Lee, Tzu-Cheng; Tseng, Shin-Hua; Chu, Hsueh-Liang; Pan, Ju-Pin; Chang, Chia-Ching (My University, 2011)
Haptoglobin (Hp) is an acute phase protein that binds free hemoglobin (Hb), preventing Hb-induced oxidative damage in the vascular system. There are three phenotypes in human Hp, whose heterogeneous polymorphic structures and varying concentrations in plasma have been attributed to the cause of diseases and outcome of clinical treatments. Different phenotypes of Hp may be composed of the same subunits but different copy numbers, rendering their determination difficult by a single procedure. In this study, we have developed a simple, fast, reliable and sensitive method, using label-free nanogold-modified bioprobes coupled with self-development electrochemical impedance spectroscopy (EIS). By this method, probe surface charge transfer resistance is detected. The relative charge transfer resistance ratios for Hp 1-1, Hp 2-1 and Hp 2-2 were characterized. We were able to determine protein size difference within 3 nm, and the linear region of the calibration curve for Hp levels in the range of 90 pg ml(-1) and 90 mu g ml(-1) (similar to 1 fM to 1 pM). We surmise that similar approaches can be used to investigate protein polymorphism and altered protein-protein interaction associated with diseases.